Enhanced Predictability of Eastern North Pacific Tropical Cyclone Activity Using the ENSO Longitude Index. Issue 16 (17th August 2020) - Balaguru, Karthik; Patricola, Christina M.; Hagos, Samson M.; Leung, L. Ruby; Dong, Lu
Abstract: While El Niño–Southern Oscillation (ENSO) influences eastern North Pacific (ENP) tropical cyclones (TCs) through a variety of atmospheric processes when examined concurrently, ocean pathways dominate at longer lead times. The eastward displacement of the warm pool during an El Niño, which carries warm water into the ENP basin, is the primary oceanic mechanism. Despite this, the question of whether an accurate knowledge of preseason ENSO conditions enhances predictability of ENP TCs has not been addressed specifically. In this study, we show that relative to traditional indices of ENSO, the ENSO Longitude Index (ELI) captures changes in the location of deep convection and associated thermocline processes more accurately. Consequently, the ELI explains more variability in the upper‐ocean heat content, and thus TC activity, at lead times of several months in the ENP basin. These results motivate the need to further explore the predictability of ENP TCs associated with ENSO. Plain Language Summary: During an El Niño, the warm water that traditionally resides in the tropical western Pacific migrates to the eastern part of the basin, causing an increase in the upper‐ocean heat content and thereby enhancing tropical cyclone (TC) activity in the eastern North Pacific (ENP). This is because heat energy available at the ocean surface is extracted by storms passing over them and used as fuel for their intensification. Despite this knowledge, the question of whether an accurate information of El Niño–Southern Oscillation (ENSO) improves seasonal predictability of ENP TCs remains unanswered to date. In this study, we show that unlike traditional indices of ENSO that are based on fixed thresholds and are almost empirical, the ENSO Longitude Index (ELI) improves the predictability of ENP TCs significantly at lead times of 5–6 months facilitated by the ocean's memory. By accounting for changes in the Walker circulation, and associated east‐west shifts in the location of deep convection and warm water volume, ELI better explains interannual variations in the upper‐ocean heat content in the ENP TC basin. These results promote the potential use of the ELI for seasonal forecasts of ENP TC activity. Key Points: The ENSO Longitude Index (ELI) better predicts eastern North Pacific (ENP) tropical cyclone (TC) activity at lead times of several months The ELI outperforms traditional ENSO indices because it captures changes in ocean thermal structure associated with ENSO more accurately These results point to the need for further exploration of the role of ENSO in seasonal forecasts of ENP TCs